Pengembangan Aplikasi Android dalam Pembelajaran Menulis Cerita di Sekolah Dasar - Nurhalimah, Irma; Iswara, Prana Dwija; Aeni, Ani Nur (Academy of Education Journal, 2024)
This study aims to enhance fifth-grade students' story-writing skills by developing a Android application called Whepture, based on the analysis of prevalent issues. The application is designed using Canva, Construct 2, and Netlify. Data were collected from interviews, questionnaires, test results, and documentation. This study employed the ADDIE research model, which includes five stages: analysis, design, development, implementation, and evaluation. The Android application product assessment questionnaire was distributed to lecturers, teachers, and fifth-grade students. The results indicated that the Android application met the eligibility criteria, with a score of 95% in the material expert assessment, classified as very feasible, and 96.42% in the media expert assessment, also classified as very feasible. The student assessment evaluation yielded a 95.67% score rating the app in the very feasible category. The average student learning score was 89.11, indicating the app's effectiveness in the learning process. Despite the categorization by material and media experts and student users, other primary school students can still add value to the development of this application.